Sejarah desa: Transformasi Desa Pendung Talang Genting dari perkebunan ke kampung santri (1920-2022) - Budi Darmawan; Nuranisa Fitri (Universitas Negeri Malang, 2023)
This research aims to describe the development of Pendung Talang Genting from pre-colonial times to the independence era focus on geographical, cultural, economic and religious aspects. The method is historical with four main steps: data collection, data testing, data interpretation, and history writing. The community maintains the cultural heritage and customs of their ancestors, maintains local wisdom and Islamic values in various cultural and religious activities. Its economy depends on rice farming and fishing. This village has existed since before Dutch colonialism in Kerinci, and separated from Kemendapoan Seleman in Dutch colonial era, and experienced economic and political interference from the colonials because of its Coffee comodity. With economic development and the influence of Islam, people increased their understanding of religion, which continued until Indonesian independence. In 2009, the Islamic boarding school in Pendung Talang Genting was reopened to strengthen Islamic education and life. Village regulations were also adopted to regulate the community's religious and cultural activities, including rules relating to the wearing of the hijab, participation in Al-Qur'an recitations, and the prohibition of alcohol and drugs. For decades, Pendung Talang Genting Village has maintained its identity as a